Pengelolaan Badan Usaha Milik Desa (BUMDES) Lancar Jaya Di Desa Mejing Sebagai Upaya Meningkatkan Kemandirian Desa - Nicodemus Christian Aribowo; Kamala Aprelia Sari (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
The central government gives authority to regional governments and economic institutions at the village level to develop their own regions with a focus on improving the economy and people's welfare. The reality in the field is that many villages fail to run Village-Owned Enterprises due to the lack of preparedness of managers and the lack of village potential. The purpose of this study is to determine the condition and governance of a developing Village Owned Enterprise. The method used is a qualitative approach. The results of the study show that the Lancar Jaya Village-Owned Enterprise has succeeded in improving the economy of Mejing Village in accordance with the objectives of establishing a Village-Owned Enterprise. However, there are still obstacles in the management of Village-Owned Enterprises such as a lack of management skills, rent payments to the village government, and sustainable business plans. The solutions provided include providing business management training, improving financial supervision and management, and marketing production products through social media platforms as a digital marketing strategy.